Preparation of core-shell structure heat-conducting filler and application of core-shell structure heat-conducting filler in two-component heat-conducting structural adhesive
The core-shell structure thermal filler coated with aluminum oxide is formed by ultrasonic atomization, which solves the problem of water absorption and agglomeration of aluminum nitride, improves its thermal conductivity, and achieves good performance in two-component thermal conductivity structural adhesives.
Patent Information
- Application Number
- CN202411491876.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-28
AI Technical Summary
The aluminum nitride thermal filler is prone to water absorption and agglomeration, resulting in its performance degradation, and the existing modification methods are not ideal.
Ultrasonic atomization method is used to mix the modified aluminum nitride powder with aluminum brine solution to form a core-shell structure thermal filler coated with alumina, combining surface chemical modification and coating modification.
It effectively prevents the hydrolysis of aluminum nitride, improves its practicality, improves thermal conductivity, and achieves good dispersion and filling rate in two-component thermally conductive structural adhesives.
Smart Images

Figure BDA0005100294820000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive adhesives, and in particular to the preparation of a core-shell structure thermal conductive filler and its application in a two-component thermal conductive structural adhesive. Background Art
[0002] Thermally conductive structural adhesive is a composite material used for bonding and heat transfer at the interface between heating and cooling elements, with good thermal conductivity, electrical insulation and bonding properties. This structural adhesive has a wide range of applications, covering aerospace, energy storage, electronics industry, new energy vehicle industry and other fields. With the rapid development of the electronics industry and new energy vehicles, the problem of thermal management has become increasingly prominent. In order to ensure the normal operation and reliability of power devices such as chips, electronic controls, and batteries, higher requirements are placed on the heat dissipation, structural bonding and vibration fatigue resistance of the products. In the research and development of thermally conductive structural adhesives, thermally conductive fillers have a decisive influence on the performance of the entire adhesive. Aluminum nitride is known as the king of thermal conductivity among inorganic non-metallic materials. It is one of the few materials with high thermal conductivity and electrical insulation. In addition, it also has extraordinary thermal shock resistance and excellent corrosion resistance. It is an ideal thermal conductive material, especially suitable for fields with high thermal conductivity requirements. The only drawback is that aluminum nitride easily absorbs moisture and oxygen, causing hydrolysis and oxidation on its surface, which affects its performance. At the same time, aluminum nitride has high surface energy, powders are easy to agglomerate, and it is difficult to disperse in polymer materials.
[0003] At present, the commonly used traditional methods mainly include heat treatment, which is relatively simple in process and low in cost. Although it can achieve a certain anti-hydrolysis effect, the nitrogen content of aluminum nitride will be greatly lost, which has a great impact on the performance of aluminum nitride; the surface chemical modification method is completed by chemical reaction or chemical adsorption between the surface modifier and the particle surface, and the polymer long chain is grafted on the powder surface. The long chain containing hydrophilic groups in the polymer acts as a three-dimensional barrier in the water medium through hydration extension, but in existing research reports, the hydrolysis resistance of some modified AlN powders is still not ideal. Coating modification is a traditional modification method with a long application time. It is to coat the surface of AlN powder with inorganic compounds or organic compounds to weaken or shield the agglomeration of particles. Compared with the traditional coating modification method, the ultrasonic spray method has a fast reaction speed, and the droplets produced by atomization are uniform in size and distribution, so that the prepared powder particle size distribution is uniform. Summary of the invention
[0004] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a preparation method of a core-shell structured thermally conductive filler and its application in a two-component thermally conductive structural adhesive, combining surface chemical modification with coating modification to solve the problems of easy water absorption and agglomeration of aluminum nitride thermally conductive fillers in the prior art and to obtain a thermally conductive structural adhesive with better performance.
[0005] To achieve the above object and other related objects, the present invention provides a method for preparing a core-shell structured thermally conductive filler, comprising the following steps:
[0006] (1) Modifying the surface of aluminum nitride powder;
[0007] (2) mixing the modified aluminum nitride powder with an aluminum salt aqueous solution to obtain a precursor solution;
[0008] (3) Ultrasonic atomization is used to form a modified aluminum nitride powder coated with aluminum oxide, i.e., a core-shell structure thermal conductive filler, from the precursor solution at high temperature.
[0009] The present invention also provides a core-shell structured thermal conductive filler, which is prepared by the preparation method described above.
[0010] The present invention also provides a use of the core-shell structured thermally conductive filler as described above in a two-component thermally conductive structural adhesive.
[0011] The present invention also provides a two-component thermally conductive structural adhesive, comprising the following raw materials in parts by weight:
[0012] Component A: 30-50 parts of bisphenol A epoxy resin, 1-2 parts of fumed silica, 5-10 parts of dibutyl phthalate, 2-5 parts of coupling agent, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers with different particle sizes;
[0013] Component B: 10-15 parts of polythiol B300, 5-10 parts of polyetheramine D230, 0-1.5 parts of fumed silica, 3-6 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 1-2 parts of aluminum hydroxide, and 180-240 parts of core-shell structure thermal conductive fillers of different particle sizes.
[0014] The present invention also provides a method for preparing the two-component thermally conductive structural adhesive as described above, comprising the following steps:
[0015] S1. Mix 30-50 parts of bisphenol A epoxy resin, 1-2 parts of fumed silica, 5-10 parts of dibutyl phthalate, 2-5 parts of coupling agent, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers of different particle sizes. The core-shell structure thermal conductive fillers are divided into multiple equal parts and added in batches for mixing. After adding the core-shell structure thermal conductive fillers to each batch, vacuum stirring is performed by a three-stage stirring method to mix the slurry, so as to obtain a slurry of component A.
[0016] S2, 10-15 parts of polythiol B300, 5-10 parts of polyetheramine D230, 0-1.5 parts of fumed silica, 3-6 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 1-2 parts of flame-retardant thermally conductive powder aluminum hydroxide, and 160-240 parts of core-shell structure thermally conductive fillers of different particle sizes are mixed, the core-shell structure thermally conductive fillers are divided into multiple equal parts and added in batches for mixing, and after adding the core-shell structure thermally conductive fillers to each batch, vacuum stirring is performed by a three-stage stirring method to mix the slurry to obtain component B slurry;
[0017] S3. Stir the A component slurry and the B component slurry in a ratio of 1:1, mix well, and defoam to obtain a two-component thermal conductive structural adhesive.
[0018] The present invention also provides an application of the above-mentioned two-component thermally conductive structural adhesive in new energy vehicle batteries.
[0019] As described above, the preparation of the core-shell structure thermal conductive filler of the present invention and its application in a two-component thermal conductive structural adhesive have the following beneficial effects:
[0020] The present invention realizes the complete coating of spherical aluminum nitride by aluminum oxide by ultrasonic atomization. The presence of the aluminum oxide shell on the surface prevents the hydrolysis of aluminum nitride, thereby improving the practicality of aluminum nitride powder. Compared with the traditional method, the reaction is basically completed in an instant, and the droplets produced by atomization are uniform in size and distribution, so that the prepared powder particle size distribution is uniform. Furthermore, the prepared core-shell structure powder has good dispersibility and high filling rate in the epoxy resin matrix, which effectively improves the thermal conductivity of the two-component thermal conductive structural adhesive.
[0021] The two-component heat-conducting structural adhesive of the present invention adopts bisphenol A epoxy resin as a matrix, and is matched with a thixotropic agent (fumed silica), a diluent (bisphenol A epoxy resin), a coupling agent, a flame retardant (aluminum hydroxide) and a modified filler to form an A component, and uses polythiol as a curing agent, and is matched with a diluent (polyether amine), a thixotropic agent (fumed silica), a accelerator (2,4,6-tris (dimethylaminomethyl) phenol), a flame retardant (aluminum hydroxide) and a modified filler to form a B component, and then the A and B components are mixed in a 1:1 ratio, which can achieve rapid curing at room temperature, making the operating environment simpler, reducing construction time, reducing costs, and achieving the effect of energy saving and emission reduction. For products with large-area adhesive application, rapid curing can achieve positioning in a short time without affecting subsequent operations, thereby greatly improving production efficiency.
[0022] The two-component thermally conductive structural adhesive of the present invention not only has good thermal conductivity and flame retardancy after curing, but also has good bonding strength, and can meet the performance requirements of thermally conductive structural adhesives for current new energy batteries. DETAILED DESCRIPTION
[0023] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0024] It should be noted that when a numerical range is disclosed herein, the above range is deemed to be continuous and includes the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all sub-ranges included therein. For example, a specified range from "1 to 10" should be deemed to include any and all sub-ranges between a minimum of 1 and a maximum of 10. Exemplary sub-ranges of ranges 1 to 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, and the like.
[0025] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; and, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0026] The first aspect of the present invention provides a method for preparing a core-shell structured thermally conductive filler, comprising the following steps:
[0027] (1) Modifying the surface of aluminum nitride powder;
[0028] (2) mixing the modified aluminum nitride powder with an aluminum salt aqueous solution to obtain a precursor solution;
[0029] (3) Ultrasonic atomization is used to form a modified aluminum nitride powder coated with aluminum oxide, i.e., a core-shell structure thermal conductive filler, from the precursor solution at high temperature.
[0030] In the method for preparing the core-shell structure thermal conductive filler of the present invention, in step (1), the modification treatment uses a coupling agent to modify the aluminum nitride powder.
[0031] Wherein, the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0032] The modification step specifically includes: dissolving a modifier in anhydrous ethanol and mixing evenly to obtain an ethanol solution of the modifier, dispersing aluminum nitride powder in anhydrous ethanol to obtain an aluminum nitride solution, then adding the ethanol solution of the modifier to the aluminum nitride solution, adjusting the pH to 8-9, 8-8.5 or 8.5-9, refluxing at 60-80°C, 60-65°C, 65-70°C, 70-75°C or 75-80°C for 4-8h, 4-5h, 5-6h, 6-7h or 7-8h, washing and filtering to obtain modified aluminum nitride powder.
[0033] The mass ratio of the modifier to aluminum nitride is 1:2-3, for example, 1:2-2.2, 1:2.2-2.4, 1:2.4-2.6, 1:2.6-2.8 or 1:2.8-3.
[0034] The ratio of the aluminum nitride powder to anhydrous ethanol is 20 g: (150-250) mL, for example 20 g: (150-160) mL, 20 g: (160-170) mL, 20 g: (170-180) mL, 20 g: (180-190) mL, 20 g: (190-200) mL, 20 g: (200-210) mL, 20 g: (210-220) mL, 20 g: (220-230) mL, 20 g: (230-240) mL or 20 g: (240-250) mL.
[0035] The mass ratio of the modifier to anhydrous ethanol is 1:(5-8), for example, 1:(5-6), 1:(6-7) or 1:(7-8).
[0036] The median particle size of the aluminum nitride (AlN) powder is 1 to 150 μm. For example, 1 to 5 μm, 5 to 10 μm, 10 to 20 μm, 20 to 30 μm, 30 to 40 μm, 40 to 50 μm, 50 to 60 μm, 60 to 70 μm, 70 to 80 μm, 80 to 90 μm, 90 to 100 μm, 100 to 110 μm, 110 to 120 μm, 120 to 130 μm, 130 to 140 μm or 140 to 150 μm. In a preferred embodiment of the present invention, the median particle size of the AlN powder is 1 to 10 μm, 20 to 30 μm, 80 to 90 μm, 140 to 150 μm. In a preferred embodiment of the present invention, the median particle size of the AlN powder is 1 μm, 10 μm, 30 μm, 90 μm, or 150 μm.
[0037] The flushing is performed using alcohol.
[0038] In the method for preparing the core-shell structure thermal conductive filler of the present invention, in step (2), the aluminum salt is selected from one or more of aluminum sulfate, aluminum nitrate, and aluminum propionate.
[0039] In the method for preparing the core-shell structure thermal conductive filler of the present invention, in step (2), the concentration of the aluminum salt aqueous solution is 1.5-2.5 mol / L, for example, 1.5-1.6 mol / L, 1.6-1.7 mol / L, 1.7-1.8 mol / L, 1.8-1.9 mol / L, 1.9-2.0 mol / L, 2.0-2.1 mol / L, 2.1-2.2 mol / L, 2.2-2.3 mol / L, 2.3-2.4 mol / L or 2.4-2.5 mol / L.
[0040] In the preparation method of the core-shell structure thermal conductive filler of the present invention, in step (2), the ratio of the modified aluminum nitride powder to the aluminum salt solution is 1g: (50-100) mL. For example, 1g: (50-55) mL, 1g: (55-60) mL, 1g: (60-65) mL, 1g: (65-70) mL, 1g: (70-75) mL, 1g: (75-80) mL, 1g: (80-85) mL, 1g: (85-90) mL, 1g: (90-95) mL, 1g: (95-100) mL.
[0041] In the preparation method of the core-shell structure thermal conductive filler of the present invention, in step (3), the high temperature is 700-900° C. For example, 700-710° C., 710-720° C., 720-730° C., 730-740° C., 740-750° C., 750-760° C., 760-770° C., 770-780° C., 780-790° C., 790-800° C., 800-810° C., 810-820° C., 820-830° C., 830-840° C., 840-850° C., 850-860° C., 860-870° C., 870-880° C., 880-890° C. or 890-900° C.
[0042] A second aspect of the present invention provides a core-shell structured thermally conductive filler, which is prepared by the preparation method described above.
[0043] A third aspect of the present invention provides a use of the core-shell structure thermally conductive filler as described above in a two-component thermally conductive structural adhesive.
[0044] The fourth invention of the present invention provides a two-component thermally conductive structural adhesive, comprising the following raw materials in parts by weight:
[0045] Component A: 30-50 parts of bisphenol A epoxy resin, 1-2 parts of fumed silica, 5-10 parts of dibutyl phthalate, 2-5 parts of coupling agent, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers with different particle sizes;
[0046] Component B: 10-15 parts of polythiol B300, 5-10 parts of polyetheramine D230, 0-1.5 parts of fumed silica, 3-6 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 1-2 parts of aluminum hydroxide, and 180-240 parts of core-shell structure thermal conductive fillers of different particle sizes.
[0047] Wherein, the bisphenol A epoxy resin in component A may be 30-32 parts, 32-34 parts, 34-36 parts, 36-38 parts, 38-40 parts, 40-42 parts, 42-44 parts, 44-46 parts, 46-48 parts or 48-50 parts;
[0048] The fumed silica in component A may be 1 to 1.2 parts, 1.2 to 1.4 parts, 1.4 to 1.6 parts, 1.6 to 1.8 parts or 1.8 to 2 parts;
[0049] The dibutyl phthalate in component A may be 5 to 6 parts, 6 to 7 parts, 7 to 8 parts, 8 to 9 parts or 9 to 10 parts;
[0050] The coupling agent in component A can be 2-3 parts, 3-4 parts or 4-5 parts;
[0051] The aluminum hydroxide in component A may be 1 to 1.2 parts, 1.2 to 1.4 parts, 1.4 to 1.6 parts, 1.6 to 1.8 parts, or 1.8 to 2 parts;
[0052] The core-shell structure thermal conductive filler in component A may be 160-165 parts, 165-170 parts, 170-175 parts, 175-180 parts, 180-185 parts, 185-190 parts, 190-195 parts, 195-200 parts, 200-205 parts, 205-210 parts, 210-215 parts, 215-220 parts, 220-225 parts, 225-230 parts, 230-235 parts or 235-240 parts;
[0053] The amount of polythiol B300 in component B may be 10 to 11 parts, 11 to 12 parts, 12 to 13 parts, 13 to 14 parts, or 14 to 15 parts;
[0054] The polyetheramine D230 in component B may be 5 to 6 parts, 6 to 7 parts, 7 to 8 parts, 8 to 9 parts or 9 to 10 parts;
[0055] The fumed silica in component B may be 0 to 0.2 parts, 0.2 to 0.4 parts, 0.4 to 0.6 parts, 0.6 to 0.8 parts, 0.8 to 1.0 parts, 1.0 to 1.2 parts, 1.2 to 1.4 parts or 1.4 to 1.5 parts;
[0056] The 2,4,6-tris(dimethylaminomethyl)phenol in component B may be 3 to 4 parts, 4 to 5 parts or 5 to 6 parts;
[0057] The aluminum hydroxide in component B may be 1 to 1.2 parts, 1.2 to 1.4 parts, 1.4 to 1.6 parts, 1.6 to 1.8 parts, or 1.8 to 2 parts;
[0058] The core-shell structure thermal conductive filler in component B can be 160-165 parts, 165-170 parts, 170-175 parts, 175-180 parts, 180-185 parts, 185-190 parts, 190-195 parts, 195-200 parts, 200-205 parts, 205-210 parts, 210-215 parts, 215-220 parts, 220-225 parts, 225-230 parts, 230-235 parts or 235-240 parts.
[0059] In the two-component heat-conductive structural adhesive of the present invention, the bisphenol A type epoxy resin is selected from one or more of bisphenol A type epoxy resin E51 and bisphenol A type epoxy resin 828EL.
[0060] In the two-component thermally conductive structural adhesive of the present invention, the coupling agent is selected from one or more of isopropyl triisostearate titanate, isopropyl trioleate titanate, γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and γ-methacryloxypropyl trimethoxysilane.
[0061] A fourth aspect of the present invention provides a method for preparing the two-component thermally conductive structural adhesive as described above, comprising the following steps:
[0062] S1. Mix 30-50 parts of bisphenol A epoxy resin, 1-2 parts of fumed silica, 5-10 parts of dibutyl phthalate, 2-5 parts of coupling agent, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers of different particle sizes. The core-shell structure thermal conductive fillers are divided into multiple equal parts and added in batches for mixing. After adding the core-shell structure thermal conductive fillers to each batch, vacuum stirring is performed by a three-stage stirring method to mix the slurry, so as to obtain a slurry of component A.
[0063] S2, 10-15 parts of polythiol B300, 5-10 parts of polyetheramine D230, 0-1.5 parts of fumed silica, 3-6 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers of different particle sizes are mixed, the core-shell structure thermal conductive fillers are divided into multiple equal parts and added in batches for mixing, and after adding the core-shell structure thermal conductive fillers to each batch, vacuum stirring is performed by a three-stage stirring method to mix the slurry to obtain component B slurry;
[0064] S3. Stir the A component slurry and the B component slurry in a ratio of 1:1, mix well, and defoam to obtain a two-component thermal conductive structural adhesive.
[0065] In the preparation method of the two-component thermal conductive structural adhesive of the present invention, in step S1 and step S2, the three-stage stirring method specifically includes: the first stage is low-speed premixing, the time is 10-20s, 10-12s, 12-14s, 14-16s, 16-18s or 18-20s, the speed is 800-1200r / min, 800-850r / min, 850-900r / min, 900-950r / min min, 950-1000r / min, 1000-1050r / min, 1050-1100r / min, 1100-1150r / min or 1150-1200r / min; the purpose is to premix all the materials together; the second stage of high-speed stirring, the time is 20-30s, 20-22s, 22-24s, 24-26s, 26-28s or 28-30s, speed 1 500~2000r / min, 1500~1550r / min, 1550~1600r / min, 1600~1650r / min, 1650~1700r / min, 1700~1750r / min, 1750~1800r / min, 1800~1850r / min, 1850~1900r / min, 1900~1950r / min Or 1950~2000r / min; the third stage of vacuum defoaming, the speed is 600~800r / min, 600~650r / min, 650~700r / min, 700~750r / min or 750~800r / min, the time is 60~120s, 60~70s, 70~80s, 80~90s, 90~100s, 100~110s or 110~120s.
[0066] In the method for preparing the two-component thermally conductive structural adhesive of the present invention, the stirring speed in step S3 is 1000-1200 r / min, for example, 1000-1050 r / min, 1050-1100 r / min, 1100-1150 r / min or 1150-1200 r / min.
[0067] In the method for preparing the two-component thermally conductive structural adhesive of the present invention, the stirring time in step S3 is 60 to 90 seconds, for example, 60 to 65 seconds, 65 to 70 seconds, 70 to 75 seconds, 75 to 80 seconds, 80 to 85 seconds or 85 to 90 seconds.
[0068] In the method for preparing the two-component thermally conductive structural adhesive of the present invention, the multiple equal portions in step S2 and step S3 are 2 to 4 equal portions, such as 2 to 3 equal portions or 3 to 4 equal portions. In a preferred embodiment of the present invention, the multiple equal portions are 3 equal portions.
[0069] In the preparation method of the two-component thermally conductive structural adhesive of the present invention, the mass of the core-shell structure thermally conductive fillers with different particle sizes in step S2 and step S3 is 1μm: 10μm: 30μm: 90μm: 150μm = 0~1: 0~2: 0~3: 0~6: 0~9, and the amount of the core-shell structure thermally conductive fillers with different particle sizes cannot be 0 at the same time. Among them, the particle sizes of 1μm, 10μm, 30μm, 90μm, and 150μm are the median particle sizes of the raw material AlN powder, that is, the mass ratio of the core-shell structure thermally conductive fillers prepared with AlN powders with median particle sizes of 1μm, 10μm, 30μm, 90μm, and 150μm is 0~1: 0~2: 0~3: 0~6: 0~9. The mass ratio of the core-shell structure thermal conductive filler with different particle sizes can be 0-0.5: 0-2: 0-3: 0-6: 0-9, 0.5-1: 0-2: 0-3: 0-6: 0-9, 0-1: 0-0.5: 0-3: 0-6: 0-9, 0-1: 0.5-1: 0-3: 0-6: 0-9, 0-1: 1-1.5: 0-3: 0-6: 0-9, 0-1: 1.5-2: 0-3: 0-6: 0-9, 0-1: 0-2: 0-1: 0-6: 0-9, 0-1: 0-2: 0-1: 0-2: 0-1: 0-2: 0-1: 0-2: 6:0~9, 0~1:0~2:2~3:0~6:0~9, 0~1:0~2:0~3:0~2:0~9, 0~1:0~2:0~3:2~4:0~9, 0~1:0~2:0~3:4~6:0~9, 0~1:0~2:0~3:0~6:0~2, 0~1:0~2:0~3:0~6:2~4, 0~1:0~2:0~3:0~6:4~6, 0~1:0~2:0~3:0~6:6~8 or 0~1:0~2:0~3:0~6:8~9.
[0070] The fifth invention of the present invention provides an application of the two-component thermally conductive structural adhesive as described above in new energy vehicle batteries.
[0071] Example 1
[0072] Preparation of core-shell structure thermal conductive filler:
[0073] (1) 20 g of AlN spherical powder with a median particle size of 1 μm was weighed and dispersed in 200 mL of anhydrous ethanol, and then γ-glycidyloxypropyltrimethoxysilane was dissolved in ethanol (according to the mass ratio of γ-glycidyloxypropyltrimethoxysilane:ethanol=1:5) and stirred evenly, and then added to the AlN solution, and ammonia water was added to adjust the pH value of the solution to 8, and refluxed and stirred at 80°C for 6 hours, and then washed with alcohol and filtered to obtain modified aluminum nitride powder;
[0074] (2) taking 500 mL of 2 mol / L aluminum sulfate solution, adding 10 g of the modified aluminum nitride powder obtained in step (1), and stirring thoroughly to form a precursor solution;
[0075] (3) The precursor solution obtained in step (2) is injected into the ultrasonic atomizer from the fractal funnel. The dispersion is ultrasonically vibrated into small droplets of uniform size, and then enters the high-temperature zone of the tubular furnace driven by the carrier gas high-purity nitrogen. The tubular furnace is heated to a high-temperature zone temperature of 900°C, and is transported to the collector at the end of the tubular furnace via the carrier gas N2. The spray decomposition particles are collected in the collector at the end of the tube, and a core-shell structure thermal conductive powder is obtained.
[0076] (4) Aluminum nitride with median particle sizes of 10 μm, 30 μm, 90 μm, and 150 μm were prepared using the same method as above to obtain core-shell structured thermal conductive powders.
[0077] (5) The prepared core-shell structured thermally conductive powder has good dispersibility and high filling rate in the epoxy resin matrix.
[0078] Example 2
[0079] Preparation of two-component thermal conductive structural adhesive:
[0080] S1, 40 parts of bisphenol A epoxy resin E51, 1 part of fumed silica, 10 parts of dibutyl phthalate, 5 parts of γ-glycidyloxypropyltrimethoxysilane, 2 parts of aluminum hydroxide and 240 parts of core-shell structure thermal conductive fillers with different particle sizes (the core-shell structure thermal conductive fillers with different particle sizes are made of aluminum nitride powders of 1 μm, 10 μm, 30 μm, 90 μm and 150 μm in Example 1, respectively, with a mass ratio of 1 μm: 10 μm: 30 μm: 90 μm: 150 μm = 1:2:3:6:9) are mixed, and a non The intervention homogenizer performs vacuum stirring, wherein the core-shell structure thermal conductive filler is divided into three equal parts and added in three batches, and three-stage stirring is performed after each addition of the core-shell structure thermal conductive filler: the first stage is low-speed premixing, the purpose is to premix all materials together, the time is 20s, the speed is 1200r / min; the second stage is high-speed stirring, the time is 30s, the speed is 2000r / min; the third stage is vacuum defoaming, the speed is 800r / min, and the time is 90s; after the three stirrings are completed, the slurry is mixed to obtain the A component slurry;
[0081] S2, 15 parts of polythiol B300, 10 parts of polyetheramine D230, 1.5 parts of fumed silica, 5 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 2 parts of aluminum hydroxide and 200 parts of core-shell structure thermal conductive fillers with different particle sizes (the core-shell structure thermal conductive fillers with different particle sizes are made of aluminum nitride powders of 1 μm, 10 μm, 30 μm, 90 μm and 150 μm in Example 1, respectively, with a mass ratio of 1 μm: 10 μm: 30 μm: 90 μm: 150 μm = 1: 2: 3: 6: 9) are mixed and the mixture is stirred for 10 minutes by non-intervention homogenization. The core-shell structure thermal conductive filler is added in three equal parts and in three batches. After each addition of the core-shell structure thermal conductive filler, three-stage stirring is performed: the first stage is low-speed premixing, the purpose is to premix all the materials together, the time is 20s, the speed is 1200r / min; the second stage is high-speed stirring, the time is 30s, the speed is 2000r / min; the third stage is vacuum defoaming, the speed is 800r / min, and the time is 90s; after the three stirrings are completed, the slurry is mixed to obtain the B component slurry;
[0082] S3. Stir the A component slurry and the B component slurry at a ratio of 1:1 (speed 1000 r / min, stirring 90 s), mix and defoam to obtain a two-component thermal conductive structural adhesive.
[0083] Example 3
[0084] Preparation of two-component thermal conductive structural adhesive:
[0085] S1, 40 parts of bisphenol A epoxy resin 828EL, 8 parts of dibutyl phthalate, 5 parts of γ-methacryloxypropyltrimethoxysilane, 1 part of aluminum hydroxide and 200 parts of core-shell structure thermal conductive fillers with different particle sizes (the core-shell structure thermal conductive fillers with different particle sizes are made of aluminum nitride powders of 10 μm, 30 μm, 90 μm and 150 μm in Example 1, respectively, with a mass ratio of 10 μm: 30 μm: 90 μm: 150 μm = 1: 2: 5: 9) are mixed, and a non-dielectric The heat conductive filler with core-shell structure is added in three equal parts and in three batches. After each addition of the heat conductive filler with core-shell structure, three-stage stirring is performed: the first stage is low-speed premixing, the purpose is to premix all materials together, the time is 15s, the speed is 1000r / min; the second stage is high-speed stirring, the time is 20s, the speed is 1800r / min; the third stage is vacuum defoaming, the speed is 800r / min, and the time is 70s; after the three stirrings are completed, the slurry is mixed to obtain the A component slurry;
[0086] S2, 12 parts of polythiol B300, 10 parts of polyetheramine D230, 5 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 2 parts of aluminum hydroxide and 160 parts of core-shell structure thermal conductive fillers with different particle sizes (the core-shell structure thermal conductive fillers with different particle sizes are made of aluminum nitride powders of 10 μm, 30 μm, 90 μm and 150 μm in Example 1, respectively, with a mass ratio of 10 μm: 30 μm: 90 μm: 150 μm = 1: 2: 5: 9) are mixed, and vacuum stirred using a non-invasive homogenizer, wherein The core-shell structure thermal conductive filler is divided into three equal parts and added in three batches. After each addition of the core-shell structure thermal conductive filler, three-stage stirring is performed: the first stage is low-speed premixing, the purpose is to premix all materials together, the time is 15s, the speed is 1000r / min; the second stage is high-speed stirring, the time is 20s, the speed is 1800r / min; the third stage is vacuum defoaming, the speed is 800r / min, and the time is 70s; after the three stirrings are completed, the slurry is mixed to obtain the B component slurry;
[0087] S3. Stir the A component slurry and the B component slurry at a ratio of 1:1 (speed 1000 r / min, stirring 60 s), mix and defoam to obtain a two-component thermal conductive structural adhesive.
[0088] Example 4
[0089] Preparation of two-component thermal conductive structural adhesive:
[0090] S1, 40 parts of bisphenol A epoxy resin E51, 1.5 parts of fumed silica, 6 parts of dibutyl phthalate, 5 parts of γ-methacryloxypropyltrimethoxysilane, 1 part of aluminum hydroxide and 180 parts of core-shell structure thermal conductive fillers with different particle sizes (the core-shell structure thermal conductive fillers with different particle sizes are made from aluminum nitride powders of 1 μm, 10 μm, 90 μm and 150 μm in Example 1, respectively, with a mass ratio of 1 μm: 10 μm: 90 μm: 150 μm = 1:2:3:6) The core-shell structure thermal conductive filler is divided into three equal parts and added in three batches. After each addition of the core-shell structure thermal conductive filler, three-stage stirring is performed: the first stage is low-speed premixing, the purpose is to premix all the materials together, the time is 20s, the speed is 800r / min; the second stage is high-speed stirring, the time is 30s, the speed is 2000r / min; the third stage is vacuum degassing, the speed is 600r / min, and the time is 60s. After the three stirrings are completed, the slurry is mixed to obtain the A component slurry;
[0091] S2, 10 parts of polythiol B300, 10 parts of polyetheramine D230, 1 part of fumed silica, 3 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 1 part of aluminum hydroxide and 160 parts of core-shell structure thermal conductive fillers with different particle sizes (the core-shell structure thermal conductive fillers with different particle sizes are made from aluminum nitride powders of 1 μm, 10 μm, 90 μm and 150 μm in Example 1, respectively, with a mass ratio of 1 μm: 10 μm: 90 μm: 150 μm = 1:2:3:6) are mixed and vacuum stirred by a non-invasive homogenizer. The core-shell structure thermal conductive filler is divided into three equal parts and added in three batches. After each addition of the core-shell structure thermal conductive filler, three-stage stirring is performed: the first stage is low-speed premixing, the purpose is to premix all the materials together, the time is 20s, the speed is 800r / min; the second stage is high-speed stirring, the time is 30s, the speed is 2000r / min; the third stage is vacuum degassing, the speed is 600r / min, and the time is 60s; after the three stirrings are completed, the slurry is mixed to obtain the B component slurry;
[0092] S3. Stir the A component slurry and the B component slurry at a ratio of 1:1 (speed 1000 r / min, stirring 60 s), mix and defoam to obtain a two-component thermal conductive structural adhesive.
[0093] Example 5
[0094] Preparation of two-component thermal conductive structural adhesive:
[0095] The difference from Example 2 is that during the preparation process, bisphenol A epoxy resin E51 is replaced by bisphenol A epoxy resin E51 and 828EL mixed in a mass ratio of 1:1, and the remaining steps are the same as Example 2; a two-component thermally conductive structural adhesive is prepared.
[0096] Comparative Example 1
[0097] The difference from Example 2 is that during the preparation process, the core-shell structure thermal conductive filler is replaced with untreated aluminum nitride spherical powder, and the remaining steps are the same as Example 2; a two-component thermal conductive structural adhesive is prepared.
[0098] Comparative Example 2
[0099] The difference from Example 2 is that during the preparation process, polythiol B300 is replaced by polythiol VT4300, and the remaining steps are the same as those of Example 2; a two-component thermally conductive structural adhesive is prepared.
[0100] Performance Testing:
[0101] The material properties of the epoxy thermal conductive structural adhesives of Examples 2 to 5 and Comparative Examples 1 to 2 are shown in Table 1:
[0102] Table 1
[0103]
[0104] It can be seen from Table 1 that the bonding strength, tensile strength and elongation at break of the thermally conductive adhesives prepared in Examples 1 to 5 are significantly better than those in Comparative Examples 1 to 2. In comprehensive comparison, the thermally conductive adhesives prepared in Examples 1 to 5 have better comprehensive performance than those in Comparative Examples 1 to 2.
[0105] In summary, the present invention realizes the complete encapsulation of spherical aluminum nitride by aluminum oxide through ultrasonic atomization, and the presence of the aluminum oxide shell on the surface prevents the hydrolysis of aluminum nitride, thereby improving the practicality of aluminum nitride powder; the two-component thermal conductive structural adhesive of the present invention uses bisphenol A type epoxy resin, fumed silica, dibutyl phthalate, coupling agent, aluminum hydroxide and core-shell structure thermal conductive filler as component A, and uses polythiol B300, polyetheramine D230, fumed silica, 2,4,6-tris(dimethylaminomethyl)phenol, aluminum hydroxide and core-shell structure thermal conductive filler as component B, and component A is mixed with component B to obtain a two-component thermal conductive structural adhesive. The two-component thermal conductive structural adhesive prepared by the present invention can achieve rapid curing at room temperature, making the operating environment simpler, reducing construction time, reducing costs, and achieving the effect of energy saving and emission reduction; for products with large-area adhesive application, rapid curing can achieve positioning in a short time without affecting subsequent operations, thereby greatly improving production efficiency. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.
[0106] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a core-shell structured thermally conductive filler, characterized in that: The following steps are involved: (1) Modifying the surface of aluminum nitride powder; (2) mixing the modified aluminum nitride powder with an aluminum salt aqueous solution to obtain a precursor solution; (3) Ultrasonic atomization is used to form a modified aluminum nitride powder coated with aluminum oxide, i.e., a core-shell structure thermal conductive filler, from the precursor solution at high temperature.
2. The method for preparing the core-shell structure thermal conductive filler according to claim 1, characterized in that: Also includes one or more of the following features: A) in step (1), the modification treatment uses a coupling agent to modify the aluminum nitride powder; B) in step (2), the aluminum salt is selected from one or more of aluminum sulfate, aluminum nitrate, and aluminum propionate; C) in step (2), the concentration of the aluminum salt aqueous solution is 1.5 to 2.5 mol / L; D) In step (2), the ratio of the modified aluminum nitride powder to the aluminum salt solution is 1 g: (50-100) mL; E) In step (3), the high temperature is 700-900°C.
3. The method for preparing the core-shell structure thermal conductive filler according to claim 2, characterized in that: Also includes one or more of the following features: A1) the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; A2) The modification step specifically includes: dissolving the modifier in anhydrous ethanol and mixing evenly to obtain an ethanol solution of the modifier, dispersing the aluminum nitride powder in anhydrous ethanol to obtain an aluminum nitride solution, and then adding the ethanol solution of the modifier to the aluminum nitride solution, adjusting the pH to 8-9, refluxing at 60-80° C. for 4-8 hours, washing, and filtering to obtain modified aluminum nitride powder.
4. A core-shell structure thermal conductive filler, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the core-shell structure thermally conductive filler as claimed in claim 4 in a two-component thermally conductive structural adhesive.
6. A two-component thermally conductive structural adhesive, characterized in that: The raw materials include the following components in parts by weight: Component A: 30-50 parts of bisphenol A epoxy resin, 1-2 parts of fumed silica, 5-10 parts of dibutyl phthalate, 2-5 parts of coupling agent, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers with different particle sizes; Component B: 10-15 parts of polythiol B300, 5-10 parts of polyetheramine D230, 0-1.5 parts of fumed silica, 3-6 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers of different particle sizes.
7. The two-component thermally conductive structural adhesive according to claim 6, characterized in that: The bisphenol A epoxy resin is selected from one or more of bisphenol A epoxy resin E51 and bisphenol A epoxy resin 828EL; And / or, the coupling agent is selected from one or more of isopropyl triisostearate titanate, isopropyl trioleate titanate, γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and γ-methacryloxypropyl trimethoxysilane.
8. A method for preparing a two-component thermally conductive structural adhesive as claimed in any one of claims 6 to 7, characterized in that: The following steps are involved: S1. Mix 30-50 parts of bisphenol A epoxy resin, 1-2 parts of fumed silica, 5-10 parts of dibutyl phthalate, 2-5 parts of coupling agent, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers of different particle sizes. The core-shell structure thermal conductive fillers are divided into multiple equal parts and added in batches for mixing. After adding the core-shell structure thermal conductive fillers to each batch, vacuum stirring is performed by a three-stage stirring method to mix the slurry, so as to obtain a slurry of component A. S2, 10-15 parts of polythiol B300, 5-10 parts of polyetheramine D230, 0-1.5 parts of fumed silica, 3-6 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 1-2 parts of aluminum hydroxide, and 160-240 parts of core-shell structure thermal conductive fillers of different particle sizes are mixed, the core-shell structure thermal conductive fillers are divided into multiple equal parts and added in batches for mixing, and after adding the core-shell structure thermal conductive fillers to each batch, vacuum stirring is performed by a three-stage stirring method to mix the slurry to obtain component B slurry; S3. Stir the A component slurry and the B component slurry in a ratio of 1:1, mix well, and defoam to obtain a two-component thermal conductive structural adhesive.
9. The method for preparing the two-component thermally conductive structural adhesive according to claim 8, characterized in that: In step S1 and step S2, the three-stage stirring method specifically includes: the first stage is low-speed premixing, the time is 10 to 20 seconds, and the speed is 800 to 1200 r / min; the second stage is high-speed stirring, the time is 20 to 30 seconds, and the speed is 1500 to 2000 r / min; the third stage is vacuum defoaming, the speed is 600 to 800 r / min, and the time is 60 to 120 seconds; And / or, the stirring speed in step S3 is 1000-1200 r / min; And / or, the stirring time in step S3 is 60 to 90 seconds; And / or, the multiple equal portions in step S2 and step S3 are 2 to 4 equal portions; And / or, the mass ratio of the core-shell structure thermal conductive fillers with different particle sizes in step S2 and step S3 is 1μm:10μm:30μm:90μm:150μm=0~1:0~2:0~3:0~6:0~9, and the amounts of the core-shell structure thermal conductive fillers with different particle sizes cannot be 0 at the same time.
10. Use of the two-component thermally conductive structural adhesive as claimed in any one of claims 6 to 7 in new energy vehicle batteries.